Development of a Physical Education Learning Model Based on Geo Traditional Games - Irfan Irfan; Nasrullah Nasrullah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Traditional games in physical education (PE) are underutilized, limiting students’ exposure to local cultural values and hindering the development of fundamental motor and social skills. This study aims to develop and validate a physical education learning model based on Geo, a traditional game from the Bima community, to enhance motor skills, focus, and cooperation among elementary students. This research employed the ADDIE development model—Analysis, Design, Development, Implementation, and Evaluation. Participants included two PE academics, two PE teachers, and 30 elementary school students in both small- and large-scale trials. Instruments included interviews, questionnaires, and observations. Validation data were analyzed using Aiken’s V formula to assess content validity. Expert validation showed very high content validity for both the learning module (V = 0.95) and the game model (V = 0.92). In the small-scale trial, student scores averaged 74.25 (motor skills), 73.25 (focus), and 75.5 (cooperation). These improved significantly in the large-scale trial to 93.83, 93.66, and 94.50, respectively. Statistical analysis indicated a significant difference (p 0.001) and large effect sizes (Cohen’s d 2.5). The Geo-based learning model proved effective in improving students’ physical and social competencies. It also supports the integration of cultural elements into PE instruction, making learning more contextual, engaging, and meaningful. This model is a viable alternative for culturally responsive PE learning and contributes to preserving local traditions.